Psychiatric and behavioral disorders in patients undergoing opioid agonist maintenance therapy - Halytska-Pasichnyk , N.R. (Medicni Perspektivi, 2025)
The aim of this study was to analyze anxiety, depression, aggression, cognitive impairments, and quality of life in patients receiving methadone maintenance therapy. The study was conducted in 2024 at one of the methadone maintenance therapy sites of the Municipal Enterprise «Dnipropetrovsk multidisciplinary clinical hospital for the provision of psychiatric care» Dnipropetrovsk Regional Council». A total of 150 patients aged 26 to 64 years participated in the study, including 117 (78.0%) men and 33 (22.0%) women. The participants were divided into the main group (101 individuals) and the comparison group (49 individuals). The study employed clinical-anamnestic, clinical-psychopathological, and psychodiagnostic methods, including the Symptom Checklist-90-Revised (SCL-90-R), the Hamilton Anxiety Rating Scale (HAM-A), the Hamilton Depression Rating Scale (HAM-D), the Buss-Durkee Hostility Inventory, the Montreal Cognitive Assessment (MoCA), and the World Health Organization Quality of Life Brief Questionnaire (WHOQOL-BREF). The results indicated that the median levels of depression 13,0 [7,0; 19,0] and anxiety 15,0 [8,0; 22,0] in the total sample and both groups corresponded to a mild severity. Most patients exhibited mild anxiety (60,7%). Depression assessment revealed that the majority of patients either had no depression (28,7%) or presented with mild symptoms (24,0%). The majority of participants had no cognitive impairment (45,3%) or only mild deficits (54,7%). Patients demonstrated normal levels of aggression 19,0 [16,0; 24,0] but exhibited an increased level of hostility 10,0 [8,0; 12,0]. At baseline, mild anxiety and depressive symptoms predominated among patients receiving methadone therapy. Elevated hostility was observed, whereas overall aggression remained within the normative range. Cognitive impairment was absent or mild. These baseline findings may inform the development of differentiated treatment strategies for this cohort.